7+4(5x-4)=8-3(2x+1)

Simple and best practice solution for 7+4(5x-4)=8-3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+4(5x-4)=8-3(2x+1) equation:


Simplifying
7 + 4(5x + -4) = 8 + -3(2x + 1)

Reorder the terms:
7 + 4(-4 + 5x) = 8 + -3(2x + 1)
7 + (-4 * 4 + 5x * 4) = 8 + -3(2x + 1)
7 + (-16 + 20x) = 8 + -3(2x + 1)

Combine like terms: 7 + -16 = -9
-9 + 20x = 8 + -3(2x + 1)

Reorder the terms:
-9 + 20x = 8 + -3(1 + 2x)
-9 + 20x = 8 + (1 * -3 + 2x * -3)
-9 + 20x = 8 + (-3 + -6x)

Combine like terms: 8 + -3 = 5
-9 + 20x = 5 + -6x

Solving
-9 + 20x = 5 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-9 + 20x + 6x = 5 + -6x + 6x

Combine like terms: 20x + 6x = 26x
-9 + 26x = 5 + -6x + 6x

Combine like terms: -6x + 6x = 0
-9 + 26x = 5 + 0
-9 + 26x = 5

Add '9' to each side of the equation.
-9 + 9 + 26x = 5 + 9

Combine like terms: -9 + 9 = 0
0 + 26x = 5 + 9
26x = 5 + 9

Combine like terms: 5 + 9 = 14
26x = 14

Divide each side by '26'.
x = 0.5384615385

Simplifying
x = 0.5384615385

See similar equations:

| 3(7j+2)/4=12 | | 3(3x-9)=(x-3) | | 26+17+22+x/4 | | 9z-5c=30+c | | 5+4(5x-4)=7-3(2x+1) | | 5/6x-2/11x | | -a^2+11a=0 | | 5/6X+6/7-2/11X | | 2x+10+4(-x)=(-x)+(-20) | | 10d+5=7d+32 | | 2/5x+3=9 | | (1.49+0.59+0.49)=30.84+0.30 | | (7x-8)(3x+9)= | | fx=-1x+x^3 | | 4/5=c/7 | | 3-x-9+15x= | | 3x+(-2x)+x=3x+18 | | 3t+8=5t+8-2t | | 3(x-4)=-1.2 | | 100x-29=42671 | | 1/4x-1/8x=3-1/16x | | 60x=100 | | 7(a+2)=34.3 | | x*3=18 | | 0.25y-3.5=0.15y+1-0.8y | | 100x-29=100(426.71) | | -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m |

Equations solver categories